Uncertainty estimation in environmental road traffic noise measurements using ISO 1996-2:2017 - Simona Domazetovska, Maja Anachkova, Viktor Gavriloski, Vasko Changoski (EuroRegio, 2022)
When measuring the road traffic noise, the environmental noise levels are quantitatively described using the equivalent noise pressure level parameter (L_eq). The value of L_eq based on the measurements done with sound level meter would probably differ from the true one due to the sources that can cause measurement uncertainty. According to this, the ISO 1996-2:2017 standard proposes calculation of the standard measurement uncertainty, so that the results from the measurements could be more accurate. This paper proposes a guideline on estimating the measurement uncertainty in compliance with the ISO standard for short-term measurements of road traffic noise. To verify the proposed method, twenty short-term measurements are done in same spot in morning and afternoon period from Monday to Friday for two weeks; and afterwards, the measurement uncertainty is calculated for each measurement. To confirm the accuracy of the results, additional acoustic modeling was made. By comparing the results for the L_eq parameter from the measurements and from the acoustic noise maps in accordance with the calculated measurement uncertainty, it could be confirmed the results accuracy. In conclusion, this paper presents a reflection on why estimation of the uncertainty of the measurement is essential in environmental noise analysis.
Keywords: uncertainty estimation, environmental noise, noise measurements, acoustic noise maps